Pengembangan Buku Ajar Menggunakan Model 4D dalam Peningkatan Keberhasilan Pembelajaran Pendidikan Agama Islam - Khaerul Fajri; Taufiqurrahman Taufiqurrahman (Jurnal Pendidikan Islam Indonesia, 2017)
It is a fact that, teachers have been accustomed to take materials as teaching materials from textbooks or textbooks provided the school and though the textbook still has many weaknesses. Among them are: (1) No Standard Competency, Basic Competency, and Indicator, (2) there are no instructional guidelines, (3) no multiple choice assessment, (4) lack of learning material on reference of reading material and (5) unsuitable laying of the Qur'an and hadith. From some of the above problems, the researcher is interested to write a scientific paper entitled Development of Textbook Using 4 D Model (Define, Design, Develop, And Disseminate) in improving success of learning in islamic studies lesson class x even semester in SMA Ibrahimy Sukorejo Situbondo on 2016/2017 year. The research method used is R & D Using Model 4 D (Define, Design, Develop, And Disseminate). Technique of data collection using test method, questionnaire, observation, interview, and documentation. while the data analysis using the test device analysis and effectiveness test. The development has resulted in one textbook product, entitled "Textbook of Islamic Education And Nature Character Class X in second Semester.”